2009
DOI: 10.1159/000193295
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Subcutaneous Tissue PO<sub>2</sub> Reflect Oxygen Metabolism of the Small Intestinal Mucosa during Hemorrhage and Resuscitation

Abstract: Background: The first tissues to be deprived of perfusion and oxygenation in a hypovolemic situation and the last ones to be reperfused are the subcutaneous tissue and the gastrointestinal mucosa. We hypothesized that measurements of subcutaneous tissue gases and pH might reflect simultaneous changes in oxygenation of the intestinal mucosa. The aim of this study was to evaluate tissue gases and pH as measures of tissue oxygenation and tissue oxygen metabolism in subcutaneous and intestinal tissues simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Intestinal pO 2 measured using a polarographic oxygen electrode placed in direct contact with the serosa of the ileum yielded baseline results similar to ours, 52± 8 [17] versus 55.5 ± 11 mmHg. The pO 2 on day 1 increased for the majority of control and SMA-banded rats.…”
Section: Discussionsupporting
confidence: 82%
“…Intestinal pO 2 measured using a polarographic oxygen electrode placed in direct contact with the serosa of the ileum yielded baseline results similar to ours, 52± 8 [17] versus 55.5 ± 11 mmHg. The pO 2 on day 1 increased for the majority of control and SMA-banded rats.…”
Section: Discussionsupporting
confidence: 82%
“…However, whereas resuscitation after induced abnormalities in gastric tonometry has shown promise in animal studies (1517), prospective studies of protocols aimed at improving splanchnic circulation have not consistently shown patient outcome benefit (18–22). Use of gastric tonometry has been impeded partially by confounding factors such as the effects of temperature (23) and pH (24) on hemoglobin affinity for CO 2 , and due to the discontinuous measurement of the method, which can take more than 10 min to acquire.…”
Section: Introductionmentioning
confidence: 99%
“…The perfusion of the intestinal organs remained unchanged until a total blood loss of 37% of the calculated total blood volume resulted in cardiac index and blood pressure values of less than 40 ± 3 ml/kg/min and 51 ± 5 mmHg, respectively. In dogs, pigs and rats it has been shown that in a hypovolemic situation the perfusion of the skin, the skeletal muscles and the gastrointestinal tract is not a priority and is disproportionally reduced compared to the muscle tissue [ 34 36 ]. In contrast a study with nine healthy horses under isoflurane anesthesia showed that gastrointestinal perfusion was preserved until a threshold blood pressure of about 60 mmHg or cardiac output lower 50 mL/kg /min were reached [ 6 ].…”
Section: Discussionmentioning
confidence: 99%